A data-driven analysis of the technical and tactical evolution of elite women's football - Bransen, L.; Davis, J. (International Journal of Sports Science & Coaching, 2024)
Currently, most research into the evolution of player performance in women's football has focused on physical performance. In contrast, we lack data-driven research into the technical and tactical developments of the women's game. This paper aims to fill this research gap by analysing an extensive longitudinal dataset containing event data for 3510 matches over eight years in the game's top leagues. It uses analytics techniques to assess changes in technical skills and tactical behaviours in the women's game. Tactically, we observe longer possession sequences and fewer long-distance shots. Technically, we observe that players are completing more difficult and valuable passes at a higher rate, and putting a higher percentage of shots on target, with a particular emphasis on aiming for the corners of the goal. These findings could aid football practitioners to account for the developments of the game.